Two-dimensional electron gas in a magnetic field : the non-degenerate limit - Wang, Lipo. (2012)
The thermodynamical properties of a two-dimensional electron gas (2DEG) in a magnetic field with an arbitrary level broadening are discussed in the nondegenerate limit first proposed by Zawadzki. It is concluded that experimental measurements in the non-degenerate regime may open a new avenue for investigations on the density of states of a 2DEG in a magnetic field.